2006
DOI: 10.1038/sj.bjc.6603363
|View full text |Cite
|
Sign up to set email alerts
|

The oncolytic effect in vivo of reovirus on tumour cells that have survived reovirus cell killing in vitro

Abstract: The use of oncolytic viruses has received considerable attention in recent years and many viruses have proved to be effective against a variety of cancer models and a few are currently being used in clinical trials. However, the possible emergence and outcome of virus-resistant tumour cells has not been addressed. We previously reported the effective use of reovirus against lymphoid malignancies, including the Burkitt's lymphoma cell line Raji. Here we isolated in vitro persistently infected (PI) Raji cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 39 publications
5
34
0
Order By: Relevance
“…Previously, we showed that persistently infected cells lose tumourigenicity in vivo (Alain et al , 2006; Kim et al , 2007), and as expected, none of the three persistently infected cell lines were able to produce tumours in SCID mice. Nevertheless, mice injected with Raji PI or CA46 PI cells rapidly developed black tail syndrome (Figure 5A) and displayed severe morbidity by 3–4 weeks post-inoculation.…”
Section: Resultssupporting
confidence: 83%
“…Previously, we showed that persistently infected cells lose tumourigenicity in vivo (Alain et al , 2006; Kim et al , 2007), and as expected, none of the three persistently infected cell lines were able to produce tumours in SCID mice. Nevertheless, mice injected with Raji PI or CA46 PI cells rapidly developed black tail syndrome (Figure 5A) and displayed severe morbidity by 3–4 weeks post-inoculation.…”
Section: Resultssupporting
confidence: 83%
“…They were likely to have contributed to tumor regrowth and ultimate failure of the therapy. Several other researchers have raised the possibility of virus-resistant cancer cells [69,209,212,225,230,231], but despite promising tumor responses, e.g. to repeated dosing, none of these studies have analysed the emergence of such cells over the course of virotherapy by detailed scrutiny using both histochemistry and explant culturing.…”
Section: Resistance To Virusmentioning
confidence: 99%
“…The distinction is important, as persistently infected cells may still be susceptible to cell death via cytotoxic gene products encoded by viral vectors. Recently Alain et al [230] demonstrated using reovirus type 3 that persistently infected Raji cells (derived from Burkitt's lymphoma) could be rendered virus-free by treatment with neutralizing antibody. Remarkably, despite remaining resistant to virus in vitro, these ''cured'' cells were efficiently killed by the virus in xenografts in SCID mice.…”
Section: Resistance To Virusmentioning
confidence: 99%
“…Among the different cell lines that have been examined over the years, and that can actually support a productive reovirus infection, some of these nevertheless exhibit partial resistance to viral induced cell death at early times post-infection while eventually becoming persistently infected (see for examples: Alain et al, 2006;Danis et al, 1993;Kim et al, 2007;Taber et al, 1976;Verdin et al, 1986). However, detailed data of the kinetics and long-term cultures of (Montgomery et al, 1991), although the cells still exhibited limited cell growth once infected.…”
Section: Discussionmentioning
confidence: 99%
“…However, proteolytic uncoating of the virus by lysosomal enzymes in the infected cell is often limiting (see for examples: Golden et al, 2002;Wetzel et al, 1997a,b). Alternatively, the secretion of proteases in the external milieu could likely promote virus infection in some tissues including tumoral microenvironment (Alain et al, 2006 ;Amerongen et al, 1994;Bass et al, 1990;Bodkin et al, 1989). …”
Section: Introductionmentioning
confidence: 99%